PENINGKATAN KINERJA MELALUI DISIPLIN, MOTIVASI DAN LINGKUNGAN KERJA PADA SATUAN RESKRIM - dewi puspita fitri; Tjiptogoro Dinarjo Soehari (Akademika, 2019)
This study aims to find a model for building Police Officer’ at Satuan Reskrim Polres Metro Bekasi Kota to perform optimally. The method used in this studyis explanatory research and SPSS software for Windows version 24. The population in this study was 94 Police Officer’ at Satuan Reskrim Polres Metro Bekasi Kota by using saturated sampling method. Data Variable collected by distributing questionnaires. The number of respondents who returned questionnaire as many as 94. Variable their lack of roots is a an employee (Y ). Variabels free are discipline ( X1 ), motivation ( X2 ) and work environment ( X3 ), while Equation of Multiple Linear Regression Y= -1,561+0, 0,547x1 + 0,487x2 + 0,278x3+ e; Rsquare = 0,670, F = 60,893, Discipline is the most dominant factor in employee performance. discipline, motivation and work environment have a positive and significant influence on employee performance.The results of employee performance are -1,561, If X1, X2, and X3, are considered zero, it will affect employee performance of -1,561 if the 1-5 Likert scale is included in the not too good category